Small Countries with Volatile Revenue : Botswana and Bhutan - Kojo, Naoko C. (World Bank, Washington, DC, 2015)
Bhutan and Botswana share a number of similarities. The two countries, land locked small states, have grown rapidly over the past few decades, boosted by sustained, large-scale inflows of foreign exchange. Botswana’s annual real growth rate averaged 9 percent over the past 40 years, driven by diamond exploration, whereas Bhutan has taken full advantage of generous foreign aid inflows to achieve an average growth rate of 8 percent per year for the past 30 years. However, after decades of rapid growth, the production base of both countries remains very narrow and the economy continues to directly or indirectly dependent on government demand. Job creation, particularly for the youths, is an important policy issue. Despite these similarities, Bhutan and Botswana exhibit an interesting contrast with regard to the management of volatile foreign exchange inflows, and its macroeconomic consequences. Notwithstanding the serious impact of the recent global crisis, today Botswana’s external position remains solid, guarded by sizable international reserves and low external debt. In contrast, Bhutan has accumulated large external debt and its international reserves are under significant pressure. This paper discusses Bhutan and Botswana’s experiences with managing volatile foreign exchange inflows. It assesses the nature and domestic economic consequences of volatile flows, and analyzes the policy measures that have been used to respond to revenue volatility. The structure of the paper is as follows. Section two analyzes Botswana’s experience of managing large, volatile diamond export earnings. Section three reviews more recent experience of Bhutan. Section four draws policy lessons from the experience of two countries. Finally section five concludes the paper.